(untitled) (Linguostylistic Studies, 2021)
The article elucidates the issue of the author’s language experience, using as a case study the novel Infection by modern prose writer-intellectual S. Protsiuk. The analysis is made at the level of worldview and characterization of heroes, the author’s approach to image-creation, plot, descriptions, structure, and style. The artistic level of formation and destruction of personality in accordance with language skills, aspirations, and efforts is in the focus of the study. The language of S. Protsiuk’s artistic discourse undoubtedly reflects first of all the linguistic world of the writer, with its ideas and moods, failures and enlightenments, feelings and emotions of different amplitudes. The linguistic picture created by the modern writer is considered as the scanner of public consciousness, modifications of a mode of life. The authors seek to identify the discursive features of S. Protsiuk’s artistic epic work at the level of linguistic expression. The article sheds light on the author’s language experience bygone in the linguistic perceptions of his heroes. The emphasis is laid on the artistic originality of the author’s style in the novel Infection, reflected in the lack of dialogues, the presence of reflections and internal monologues, pictures of live conversations, and multidimensional author’s views. The study findings argue that novel Infection is a kind of struggle against the devaluation of the native language, a desire to preserve the national immune system of language conformism.